Generative Logics and Conceptual Clicks: A Case Study of the Method for Design Materialization. - Khaled, Rilla; Barr, Pippin (Design Issues)
Game design research is caught between epistemologies and disciplines, leading to a lack of grounded methodologies. Without such methodological approaches, we cannot support evidence-based claims about game design. The Method for Design Materialization (MDM) is a methodological approach to capturing game design via software version control. By embracing a time-sliced representation of a game throughout its development and pairing it with explicit materializations of design thinking through reflective writing, we believe significant progress can be made in understanding and extrapolating from the design process.